2006
DOI: 10.1164/rccm.200509-1392oc
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Monitoring of Lung Injury in Children after Acute Chlorine Exposure in a Swimming Pool

Abstract: Children acutely exposed to chlorine in a swimming pool presented a substantial lung function impairment associated with biochemical exhaled breath alterations, represented mainly by an increase in LTB(4) and a reduction in Fe(NO). Although lung function and Fe(NO) improved within a few weeks, the increased levels of exhaled LTB(4) persisted for several months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 25 publications
3
60
0
4
Order By: Relevance
“…Secondly, chronic low-grade exposure to chlorine derivatives may be related to the observed increased levels of exhaled LTB 4 in elite swimmers [4]. This observation is also supported by the findings in children accidentally exposed to chlorine, with development of respiratory symptoms, lung function impairment and exhaled breath alterations, represented mainly by an increase in LTs and a decrease in FeNO [8]. If this is the case, new therapeutic approaches that, in addition to inhaled corticosteroids, would target the 5-lipoxygenase pathway could have a role attenuating the neutrophilic airway inflammation in swimmers with asthma.…”
Section: To the Editorsmentioning
confidence: 72%
See 1 more Smart Citation
“…Secondly, chronic low-grade exposure to chlorine derivatives may be related to the observed increased levels of exhaled LTB 4 in elite swimmers [4]. This observation is also supported by the findings in children accidentally exposed to chlorine, with development of respiratory symptoms, lung function impairment and exhaled breath alterations, represented mainly by an increase in LTs and a decrease in FeNO [8]. If this is the case, new therapeutic approaches that, in addition to inhaled corticosteroids, would target the 5-lipoxygenase pathway could have a role attenuating the neutrophilic airway inflammation in swimmers with asthma.…”
Section: To the Editorsmentioning
confidence: 72%
“…This blanket statement assumes a homogeneity to idiopathic NSIP and idiopathic UIP that is contrary to the evidence. The idea of a distinct clinical phenotype for idiopathic NSIP is supported by demographic, serological and survival differences seen when IPF and idiopathic NSIP patients are compared [4][5][6], and by the differences, not similarities, seen in gene expression profiles (six of 10 published NSIP profiles are distinct from UIP while four are similar) [7,8].…”
Section: To the Editorsmentioning
confidence: 99%
“…Similar results were recently published by a German group 22 . In addition, Bonetto et al 23 reported on lung function and possible lung injury pathways in the acute phase and during a 15-month follow-up in a group of children after accidental acute chlorine exposure in a swimming pool. Right after the accident, the authors found substantial lung function impairment associated with increased leukotriene levels in exhaled breath condensate, reduced exhaled NO (measured at 50 ml/sec), and increased serum Clara cell protein (CC16) values (a sign of injury of the lung epithelial permeability barrier).…”
Section: Respiratory Effects Of Acute Chlorine Exposurementioning
confidence: 99%
“…Although lung function and exhaled NO improved within a few weeks, the levels of exhaled leukotriene B 4 remained high for several months, suggesting a neutrophilic inflammation despite the lack of any respiratory symptoms and the normalization of lung function parameters. 23 …”
Section: Respiratory Effects Of Acute Chlorine Exposurementioning
confidence: 99%
“…Considering the large blood‐tissue exchange surface area of lung tissues, serum CC16 is almost solely derived from the respiratory tract and is, therefore, considered lung‐specific. Increased circulating CC16 levels have been observed in patients with pulmonary injuries caused by inhaled ozone, chlorine, and LPS 7, 8, 9. It has been suggested as a disease marker for pulmonary sarcoidosis, chronic obstructive pulmonary disease, and severe chest trauma 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%